Professional stories: formation policies and teachers' formative pathways - Gondinho, Marta Rochelly Ribeiro; Oliveira, Luisa Xavier de; Martins, Maria da Conceição Rodrigues (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
The article presents an investigative study on professional histories in interfaces with teaching training policies. The objective of the research is based on the prerogative of analyzing teachers' histories and the reverberation of formative policies in their formative paths. For this purpose, a theoretical dialogue was held with the contributions of Nóvoa (1999) and Saviani (2009). The biographical narratives constructed from oral interviews were analyzed highlighting the analytical categories followed by the application of a semi-structured questionnaire, characterizing this study of a qualitative nature in which one takes from the narratives the subsidies for dialogue with bibliographical elements. The findings of this research indicated that teacher training policies, current legislation and the social demands of a given time have a direct influence on the individual trajectories of teachers. However, these policies are not uniform in the training paths, since each teacher builds his or her professional history based on the ways of recreating the work culture. It has also been highlighted that in the history of teacher education, given the objective conditions of practical reason, professional culture incorporates legal and formative requirements in many circumstances in an uncritical way, justifying that the normative is to be incorporated and not questioned, which highlights the hierarchical weight of policies in our modes of teaching when it consists of our primary occupation.